Inclusive School Policies: A Literature Study of Implementation Dilemmas - Rosyidi, Rizky Amalia (Journal of ICSAR, 2023)
This paper aims to examine the dilemma of implementing inclusive school policies. The method used is literature study. The inclusive school policy is a noble vision based on social justice. Even though many obstacles were found in its implementation, it is only fitting that stakeholders, in this case the government, take on a complex role in order to achieve optimal service in policy implementation. The government in this case takes the most important part in increasing the competence of teaching teachers in inclusive schools. Apart from considering competence, it is appropriate to consider support for teachers, both teaching and emotional support in order to optimize the implementation of inclusive education policies in schools, so that teachers can be confident and carry out broader exploration of teaching practices in inclusive classes. In the end, justice in access to education for all Indonesian people can be realized optimally.